Reading in a play "Memoirs of a Journalist " - قاسم غباش, وصال (Journal of College of Education, 2019)
There is no doubt that the theater in its cultural sense is necessary for the society as it as committed to an intellectual and artistic mission aimed at rooting human values and goals of any society as well as improving the taste of the recipient by developing the senses and emotions to the degree of height and elevation .Our Arab theater has defined a range of expressions in which we seek to express ourselves and the subject together .Monodrama is one the most important forms of drama used in writing ,diagnosis and directing.This is a reading of one of the Monodrama plays entitled "Memoirs of a Journalist " by the Arabic writer Gamal Mohamed Nawasreh ,which included reading :the title ,the idea of text ,personality ,language and dialogue ,conflict ,plotand the construction of the play.